IGNITION SEBAGAI INOVASI KERAMIK PADA BRAND ONIX POTTERY DENGAN MITRA UD. TRI SURYA KERAMIK - Leony Paramita; I Nyoman Ngidep Wiyasa; I Nyoman Laba (Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
Onix Pottery which is a new pilot brand that was built, the concept selection must be considered so that it can convey the message to be conveyed to the product. Onix Pottery takes the concept of Ignition, which is a foreign language for ignition. taking the Ignition concept which is applied to a new startup, namely onix pottery, is based on strong color elements and creates light that can illuminate a place. The manufacture of Onix Pottery ceramic products goes through several stages including body formation, trim, decoration which gives a touch of stone texture in accordance with the ONIX brand name (black precious stone), burning biscuits to glaze, and adding lights to support the concept. The concept of Ignition Onix Pottery produces two products named Agni and Chandara, the names are taken from the Sanskrit word for natural elements that emit light such as Agni means fire and Chandara means moon. In building new startups in the creative industry era by keeping up with digitalization developments, by utilizing internet technology that makes it easy to introduce businesses to the public. Creating content is one way to tell how the process is going to the story that the product you want to convey. In this case Onix Pottery uses the SMM (Social Media Marketing) marketing model which carries out the marketing process through social media networks. Creating interesting content, and being able to provide information that can be understood at the same time.